Brand storytelling in the digital age: challenges and opportunities in online marketing - Rachman, Rosyidah; Hamid, Mansyur Abdul; Wijaya, Bagus Kusuma; Wibowo, Sarwo Eddy; Intan, Dyah Noor (SEAN Institute, 2024)
Amidst the ever-changing landscape of the digital era, the utilization of brand storytelling has emerged as a crucial tactic in online marketing efforts. This article examines the significance of brand storytelling within the realm of digital marketing, emphasizing the obstacles and possibilities encountered by companies. This research aims to establish a conceptual model that unifies crucial features, with a specific focus on analyzing the successes and failures of brand storytelling. The qualitative research revealed that intense competition and evolving digital trends need the implementation of creative solutions. Conversely, quantitative data revealed challenges in customizing brand narratives and concerns over data privacy. In the digital era, effective brand storytelling management methods encompass several key elements: comprehensive audience analysis, tailoring narratives to individual preferences, utilizing multiple communication channels, fostering active consumer participation, and leveraging artificial intelligence technology. The results have pragmatic ramifications for enhancing online advertising tactics and fostering consumer confidence. By comprehending the advantages of brand storytelling, firms can surmount obstacles and attain a competitive edge in the constantly evolving digital era.